The Influencing Factors of Customer Trust towards KPLUS in Thailand - Boonkum, Palita; Methavasaraphak, Preecha (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
This research aims to identify and investigate the influencing factors of customer trust towards KPLUS in Thailand. The objectives of this study were: 1) to study customer trust towards KPLUS; and 2) to study the influencing factors of customer trust towards KPLUS in Thailand. The questionnaires were distributed online with a sample size of 413 using Google Forms, randomly selected through a combination of convenience sampling, snowball sampling, and purposive sampling, all falling under the non-probability sampling method. Subsequently, the information from all respondents was analyzed using the SPSS program. The study covers two analyses: descriptive analysis, and multiple regression analysis. The study results were: 1) Four crucial factors significantly influenced customer trust towards KPLUS in Thailand consist of corporate reputation, internet banking security, internet banking privacy, and perceived ease of use. These factors explained customer trust towards KPLUS in Thailand at 88.8 percent 2) The most influencing factor of customer trust towards KPLUS was internet banking security at 43.4%. This was followed by internet banking privacy, corporate reputation, and perceived ease of use respectively. 3) The study provides recommendations to assist KASIKORNBANK in improving KPLUS to garner more customer trust, recognizing customer trust as a key factor for long-term business success.